Genetic analysis of Yunnan sudden unexplained death by whole genome sequencing in Southwest of China. (February 2020) - Li, Lan-Jiang; Wang, Yue-Bing; Qu, Peng-Fei; Ma, Lin; Liu, Kai; Yang, Lin; Nie, Sheng-Jie; Xi, Yan-Mei; Jia, Peng-Lin; Tang, Xue; Sun, Zhong-Chun; Huang, Wen-li; et al.
Highlights: A family includes three people consequently died within 24 h without cause. Whole genome sequencing technology is used. Seven missense variants in cardiac and metabolic genes might be related to YNSUDs.